Herayaky Powder-Based Silage Technology for Sustainable Animal Feed in the Sejahtera Farmers Group of Nunmafo Village-North Central Timor : Teknologi Silase Berbasis Herayaky Powder Untuk Pakan Ternak Berkelanjutan Di Kelompok Tani Sejahtera Desa Nunmafo-Timor Tengah Utara - Alfred Nubatonis; Zofar Agluis Banunaek; Fried Markus Allung Blegur; Ernes Josias Blegur; Steffanie M. C. Noach; Yuliana Kolo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The availability of quality feed throughout the year is a major challenge in dryland farming, especially in Nunmafo Village, North Central Timor. The long dry season in this area results in limited green fodder. This community service program aims to apply silage technology based on Herayaky Powder to improve the quality and availability of animal feed while supporting the sustainability of animal husbandry. This technology uses King Rass grass and lamtoro leaves as the main ingredients, which are fermented with the addition of Herayaky Powder as a probiotic inoculant. Activities with Sejahtera farmer group partners are carried out through counseling and training or direct practice of silage technology. The results of animal feed processing are monitored periodically for pH levels and environmental temperatures and laboratory tests are carried out to measure the nutritional content of the feed.